The Development of Differential Mnemonic Effects of False Denials and Forced Confabulations. (24th November 2014) - Otgaar, Henry; Howe, Mark L.; Memon, Amina; Wang, Jianqin; Hobbs, Sue D.; Goodman, Gail S.
<x xml:space="preserve">Abstract</x> The current experiment was designed to assess the mnemonic consequences of false denials and forced confabulations. Children (aged 6–8 and 10–12 years) and adults viewed a video and then their memory and belief about the event were tested. Participants were then divided into three groups. In the "cued recall" condition, participants were asked to answer true‐ and false‐event questions, but could choose not to respond if they did not know the answer. In the "forced confabulation" group, participants received the same set of questions, but were forced to answer all of them. In the "false denial" group, participants were instructed to falsely deny in response to each question. One week later, participants received a source memory test, and they had to provide memory and belief ratings once more. Forced confabulations resulted in false memories in the youngest group. Moreover, our analyses showed that repeated false denials led children and adults to be highly inclined to falsely deny that they had talked to the experimenter about certain presented details, when in fact they had done so. Furthermore, false denial and non‐believed memory rates were more pronounced in younger than in older children and adults. Our results imply that denying experienced events is not a good strategy in an interviewing setting, as it adversely affects memory statements about the interview. Copyright © 2014 John Wiley & Sons, Ltd.